2015
DOI: 10.1080/00268976.2015.1011248
|View full text |Cite
|
Sign up to set email alerts
|

Excited states from range-separated density-functional perturbation theory

Abstract: We explore the possibility of calculating electronic excited states by using perturbation theory along a range-separated adiabatic connection. Starting from the energies of a partially interacting Hamiltonian, a first-order correction is defined with two variants of perturbation theory: a straightforward perturbation theory, and an extension of the Görling-Levy one that has the advantage of keeping the ground-state density constant at each order in the perturbation. Only the first, simpler, variant is tested h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…In a series of papers, Rebolini et al 171–174 considered approximate RS MC‐DFT approaches aiming at correcting excited‐state energies of the LR Hamiltonian Htrue^LR. Corrections can be derived either by considering the exact expansion in orders of μ along a range separated adiabatic connection, 172 or from the perturbation theory 173,174 . In the latter case, the Htrue^LR Hamiltonian is chosen as the unperturbed operator and the perturbation is defined as Vtrue^eeSRVtrue^SR[]ρ0, cf.…”
Section: Excited States From Rs Mc‐dftmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of papers, Rebolini et al 171–174 considered approximate RS MC‐DFT approaches aiming at correcting excited‐state energies of the LR Hamiltonian Htrue^LR. Corrections can be derived either by considering the exact expansion in orders of μ along a range separated adiabatic connection, 172 or from the perturbation theory 173,174 . In the latter case, the Htrue^LR Hamiltonian is chosen as the unperturbed operator and the perturbation is defined as Vtrue^eeSRVtrue^SR[]ρ0, cf.…”
Section: Excited States From Rs Mc‐dftmentioning
confidence: 99%
“…Equations () and (). Both Rayleigh–Schrödinger 173 and Görling–Levy 174 perturbation theories have been applied. For the i th eigenstate of Htrue^LR one recovers the pertinent eigenvalue in the 0th order.…”
Section: Excited States From Rs Mc‐dftmentioning
confidence: 99%
“…can be used as starting points for reaching the physical excitation energies by means of extrapolation techniques [36][37][38], perturbation theory [39], time-dependent linear response theory [4,5] or ensemble range-separated DFT [13,14], as discussed further in the following.…”
Section: Theorymentioning
confidence: 99%
“…In this previous work [50], a Rayleigh-Schrödinger (RS)-based perturbation theory was tested on a few atoms and molecules and it was found that the first-order excitation energies are not overall improved in comparison with the zeroth-order excitation energies. This finding was rationalized by the fact that this perturbation theory does not keep the ground-state density constant at each order.…”
Section: Introductionmentioning
confidence: 99%
“…Zeroth-order excitation energies ∆E µ k = E µ k − E µ 0 (plain line) and zeroth+first order excitation energies ∆E dashed line) in the GL-based perturbation theory for the hydrogen molecule at the equilibrium distance (top) and three times the equilibrium distance (bottom) as a function of µ. For comparison, the zeroth+first order excitation energies ∆E ) in the RS-based perturbation theory of Ref [50]. are also shown.…”
mentioning
confidence: 98%